Is heart rate variability a valuable method to investigate cardiac autonomic dysfunction in subjects with leukemia? A systematic review to evaluate its importance in clinical practice - Kirizawa, Jociele M. [UNESP]; Garner, David M.; Arab, Claudia; Valenti, Vitor E. [UNESP] (Springer Nature, 2019)
Impaired cardiovascular and autonomic function during treatment and during recovery from leukemia has been indicated. In this context, heart rate variability (HRV) is a non-invasive measure that describes the oscillations of the intervals between consecutive heart beats (RR intervals), influenced by the autonomic nervous system. We intend to review literature showing HRV changes in leukemia subjects. The articles selected in the current review were attained up to March 2018, and the search was limited to articles in English language, published in peer-reviewed journals, with both adult and child age samples. The articles were investigated in the five electronic databases: PubMed, Physiotherapy Evidence Database (PEDro), Cochrane Clinical Trials, Scientific Electronic Library Online (SciELO), and Excerpta Medica dataBASE (EMBASE). Towards the end of the research, 9 studies were included. Subjects undergoing treatment for leukemia have reduced HRV, signifying decreased vagal control of heart rate. The subjects that undertook leukemia treatment and their survivors experienced a reduction in HRV with subsequent recovery, but the recovery time is ill defined. HRV is reduced in leukemia subjects who progress to neuropathy secondary to chemotherapy, accompanied by cardiac dysfunction. We advocate the use of HRV to evaluate autonomic function and decide the treatment to prevent autonomic impairment in leukemia subjects.
Keywords: Autonomic nervous system; Cardiovascular physiology; Heart rate; Leukemia, myeloid acute, lymphoid acute